Exploring of e-WOM, Destination Image and Perceived Value toward Return to Visit - Rangga Restu Prayogo (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2021)
Factors of tourism into one of the largest and fastest way to grow an economy is suitable for a country that would like to expand it to include Indonesia. The development of tourism through promotion and maximum service is already undertaken by the authorities to attract domestic and foreign tourists in Indonesia. One of the attractions which are experiencing an increase in visiting Goa Pindul. The problems in Goa Pindul are increase tourists revisit intention, but the facilities and infrastructure are less well. The purpose of this research was to study the relationship between e-WOM, destination image, perceived value, and return to visit in the tourism industry. Sample techniques used in this research is purposive sampling using accidental sampling. Respondents who used as many as 200 respondents on travelers who already visited one time, aged 17 years, and using the internet to searching for information about Goa Pindul. Data analysis techniques used are PLS-SEM and Sobel test. The empirical results from PLS-SEM showed that e-WOM positive and significant impact on destination image, perceived value, and return to visit. The destination image has a positive and significant impact on perceived value but on return to visit insignificant. Perceived value positive and significant impact on back to visit. Sobel test findings that effect of e-WOM on arrival to visit through perceived value significantly.